Coextruded sheet
By controlling the density of the coextruded sheet and the thickness of the outer skin layer, combined with the load deflection temperature and glass transition temperature of the polycarbonate resin, the expansion, cracks and mechanical strength of the coextruded sheet during vacuum forming is solved. Problem, excellent mechanical strength and appearance design are achieved.
Patent Information
- Application Number
- CN202380051523.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-11
- Filing Date
- 2023-07-06
- Publication Date
- 2025-02-18
AI Technical Summary
During the thermal molding process such as vacuum forming, the surface of the coextruded sheet is prone to problems such as expansion and cracks, and the mechanical strength is low, making it difficult to meet the needs of high temperature and high mechanical load.
By controlling the density of the coextruded sheet, the thickness of the outer skin layer, the load deflection temperature or glass transition temperature of the resin material, ensuring uniform softening and thermal shaping between the outer skin layer and the core layer, polycarbonate resin is used as the main resin material .
It effectively suppresses surface bulge and cracks during vacuum forming, improves mechanical strength and lightness, and improves appearance design and processing performance.
Smart Images

Figure CN119486881A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to coextruded sheets comprising engineering plastics, particularly polycarbonate resins. Background Art
[0002] In recent years, foamed resins have attracted attention because they can improve convenience by making resin molded bodies lightweight and can reduce carbon dioxide emissions. The molding methods of foamed resins include physical foaming molding and chemical foaming molding. The chemical foaming molding method uses a chemical foaming agent as a foaming agent. Chemical foaming agents have a high environmental load, which is not preferred from the perspective of protecting the earth's environment. On the other hand, the physical foaming molding method uses physical foaming agents such as nitrogen and carbon dioxide as foaming agents. Physical foaming agents have a small environmental load, so they are preferred from the perspective of protecting the earth's environment. In the physical foaming molding method, as a method for foaming engineering plastics and super engineering plastics with high heat resistance, there is a method of dissolving the molten resin of engineering plastics and super engineering plastics by shear mixing with a high-pressure supercritical fluid.
[0003] Japanese Patent Gazette No. 6139038 (Patent Document 1) discloses a method for manufacturing a foamed molded body using a physical foaming agent such as nitrogen or carbon dioxide at a relatively low pressure instead of a high-pressure supercritical fluid. According to this method, a low-pressure physical foaming agent can be used to form fine foaming cells in a resin molded body in a relatively simple process without using a special high-pressure device. In addition, Patent Document 1 discloses a method for molding a foamed molded body by injection molding and extrusion molding.
[0004] Injection molding can obtain a foamed molded body of complex shape. However, the surface layer of the molten resin flows while cooling and solidifying in the mold. At this time, a non-foamed outer skin layer is formed thinly on the surface layer of the foamed molded body. On the other hand, compared with the injection molding method, the extrusion molding method has fewer restrictions on the size and load of the mold, and is suitable for continuously making a foamed molded body of a single shape and a single thickness. In addition, the sheet-like foamed molded body obtained by the extrusion molding method can be shaped into a foamed molded body of a certain degree of complex shape or a foamed molded body of a relatively large size by implementing vacuum molding, etc. However, in the extrusion molding method, when the molten resin is discharged from the mold outlet and cooled and solidified, it is difficult to form an outer skin layer on the surface layer of the foamed molded body. Compared with the foamed molded body with an outer skin layer of sufficient thickness, the foamed molded body with a thinner outer skin layer and the foamed molded body without an outer skin layer have poor surface design. In addition, the foamed molded body obtained by the extrusion molding method has the following problems: due to the pressure release when the molten resin is discharged from the mold outlet, the bubbles are destroyed, and unevenness may be generated on the surface of the foamed molded body, and the appearance design is reduced.
[0005] In addition, in Patent Document 1, there is no research on the foamed molded body of polycarbonate resin formed by vacuum-formable non-crystalline resin, nor is there any research on ensuring the surface smoothness of the foamed molded body when heated at a temperature higher than the glass transition temperature of the polycarbonate resin. Here, in the case of non-foamed resin, for crystalline resin, if heated at a temperature lower than the melting point, even at a temperature higher than the glass transition temperature, it is difficult to cause large deformation and dimensional change. However, in the case of non-foamed resin, for non-crystalline resin, when heated at a temperature higher than the glass transition temperature (the glass transition temperature of polycarbonate resin is about 145°C), thermal deformation is likely to occur. In view of this, when the foamed molded body formed by non-crystalline resin (polycarbonate resin) is heated at a temperature higher than the glass transition temperature, it is more difficult to suppress the deformation generated on its surface, such as the expansion generated on the surface of the foamed resin due to bubbles formed inside the foamed molded body or the dimensional change of the foamed molded body.
[0006] As a method for forming an outer skin layer with sufficient thickness, Japanese Patent Gazette No. 3654697 (Patent Document 2) discloses a method for manufacturing a thermoplastic resin foam sheet. According to the method for manufacturing a thermoplastic resin foam sheet, an outer skin layer can be easily formed on the surface of a thermoplastic resin foam sheet by extrusion molding. In addition, Japanese Patent Publication No. 2000-52370 (Patent Document 3) discloses a method for manufacturing a multilayer laminated molded body. The multilayer laminated molded body is formed by co-extrusion molding to form a core layer and an outer skin layer formed by a foamed resin. In the manufacturing method of Patent Document 2 and the manufacturing method of Patent Document 3, general-purpose plastics such as polypropylene or polystyrene with relatively low heat resistance and mechanical strength are used as the main resin material, and engineering plastics, particularly polycarbonate resins, with excellent heat resistance and mechanical strength are not used. In addition, the manufacturing methods of Patent Documents 2 and Patent Documents 3 are aimed at the ease or stability of the manufacture of the foamed molded body, and are not aimed at improving heat resistance and mechanical strength. In addition, if the thickness of the outer skin layer is too large, that is, the thickness of the core layer is too small, lightweighting cannot be achieved.
[0007] Japanese Patent No. 3568655 (Patent Document 4) discloses a polycarbonate resin extrusion foam laminated sheet formed by laminating a plurality of polycarbonate resin extrusion foam sheets. However, the polycarbonate resin extrusion foam laminated sheet of Patent Document 4 is a relatively thick polycarbonate resin foam sheet manufactured by cutting and laminating the polycarbonate resin extrusion foam sheets, and is not an outer skin layer that controls the surface layer.
[0008] Furthermore, the resin molded body formed by the foamed resin has a problem of reduced mechanical strength due to the low density for the purpose of improving lightness. In particular, the foamed molded body formed by the polycarbonate resin, which requires mechanical strength, also has a problem of significantly reduced mechanical strength compared to the resin molded body formed by the non-foamed resin.
[0009] Japanese Patent Publication No. 8-174780 (Patent Document 5) discloses a polycarbonate extruded resin foam laminate sheet with a high foaming ratio manufactured by a co-extrusion molding method. The polycarbonate extruded resin foam laminate sheet has excellent heating processability, especially deep drawing processability, and is also excellent in appearance design and mechanical strength. Patent Document 5 discloses the heating dimensional change when the polycarbonate extruded resin foam laminate sheet is heated in a relatively low temperature atmosphere of 170°C.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent No. 6139038
[0013] Patent Document 2: Japanese Patent No. 3654697
[0014] Patent Document 3: Japanese Patent Application Publication No. 2000-52370
[0015] Patent Document 4: Japanese Patent No. 3568655
[0016] Patent Document 5: Japanese Patent Application Laid-Open No. 8-174780 Summary of the invention
[0017] In recent years, when a coextruded sheet is thermally formed into a desired shape by vacuum forming or the like, it is required to be able to be formed at a relatively high temperature of 200°C or above and in a short time from self-sag (a phenomenon in which the molten resin sags due to its own weight) from the viewpoint of improving productivity. However, if a coextruded sheet having a core layer formed of a foamed resin and an outer skin layer formed of a non-foamed resin laminated on the main surface of the core layer is heated at a high temperature of 200°C or above, the bubbles in the core layer covered by the outer skin layer are easily thermally expanded and integrated. As a result, there is a problem that the appearance design of the coextruded sheet is deteriorated, such as the outer skin layer bulging from the main surface of the coextruded sheet or cracks in the coextruded sheet itself.
[0018] Furthermore, the core layer formed by the foamed resin is a foamed body and thus has a heat insulating effect. Therefore, in the coextruded sheet formed by laminating the core layer and the outer skin layer formed by the unfoamed resin, there may be a difference in heat conduction between the resin material of the outer skin layer and the resin material of the core layer. In the case where the coextruded sheet is thermally shaped by vacuum forming or the like, the softening degree of the core layer and the outer skin layer may differ due to the above-mentioned difference in heat conduction during heating. If thermal shaping is performed in a state where the core layer and the outer skin layer are not equally softened, the core layer and the outer skin layer will peel off, and the outer skin layer may bulge from the main surface of the coextruded sheet. Therefore, there is room for research in further suppressing the deterioration of the design of the coextruded sheet during vacuum forming.
[0019] The co-extrusion molding method is an integrated molding method in which the core layer and the outer skin layer are merged in the mold during co-extrusion molding. Therefore, when the pressure is released from the mold outlet, the bubbles in the core layer expand, and there is also a problem in making the bubble size uniform. In particular, when the pressure and concentration of the physical foaming agent are increased, the density of the expanded bubbles increases, so the bubble size of the core layer in the co-extruded sheet becomes uneven, and a bulge occurs in the co-extruded sheet after heating at 200°C or above.
[0020] In addition, although a polycarbonate laminated foamed resin sheet having a high expansion ratio as in Patent Document 5 can achieve excellent lightness, it has a problem of lower mechanical strength than a polycarbonate laminated foamed resin sheet having a low expansion ratio.
[0021] The inventors of the present invention have conducted intensive research and found that by controlling the density of the co-extruded sheet, the thickness of the outer skin layer, and either the load deflection temperature or the glass transition temperature, the mechanical strength of the co-extruded sheet including a core layer formed of a foamed resin for the purpose of weight reduction can be improved, and the deterioration of the appearance design during vacuum forming can be further suppressed.
[0022] It should be noted that Patent Document 5 does not propose to improve the mechanical strength and suppress the deterioration of the design during vacuum molding from the viewpoint of the density of the polycarbonate resin laminated foamed resin sheet and the thickness of the outer skin layer.
[0023] An object of the present disclosure is to provide a coextruded sheet containing a polycarbonate resin which can suppress surface swelling and cracking of the coextruded sheet generated during heat forming such as vacuum forming and has excellent mechanical strength.
[0024] In order to solve the above-mentioned problems, the present invention adopts the following solution. That is, the coextruded sheet of the present invention may contain a polycarbonate resin. It may have a core layer formed of a foamed resin, a first outer skin layer formed of a non-foamed resin and laminated on one main surface of the core layer, and a second outer skin layer laminated on the other main surface of the core layer. The resin materials of the first outer skin layer and the second outer skin layer may have a load deflection temperature higher than the load deflection temperature of the resin material of the core layer. The coextruded sheet may have a load deflection temperature of 0.4 to 0.9 g / cm 3 density and satisfies the following formula (1).
[0025] 0.10≤(t1+t2) / T≤0.5···(1)
[0026] In formula (1), t1 represents the thickness of the first skin layer, t2 represents the thickness of the second skin layer, and T represents the thickness of the coextruded sheet.
[0027] According to the coextruded sheet of the present disclosure, it is possible to suppress surface swelling and cracking of the coextruded sheet generated during heat forming such as vacuum forming, and to obtain excellent lightness and mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a perspective view showing a co-extruded sheet according to an embodiment.
[0029] Figure 2 Yes means Figure 1 A cross-sectional view of a coextruded sheet is shown.
[0030] Figure 3 It is a cross-sectional view showing the coextruded sheet after heating.
[0031] Figure 4 It is a cross-sectional view showing the coextruded sheet after heating.
[0032] Figure 5 This is a cross-sectional view showing a coextruded sheet including a decorative film.
[0033] Figure 6 It is a perspective view showing a mold for vacuum forming. DETAILED DESCRIPTION
[0034] (Composition 1)
[0035] In order to solve the above-mentioned problems, the present invention adopts the following solution. That is, the coextruded sheet of the present invention may contain a polycarbonate resin. It may have a core layer formed of a foamed resin, a first outer skin layer formed of a non-foamed resin and laminated on one main surface of the core layer, and a second outer skin layer laminated on the other main surface of the core layer. The resin materials of the first outer skin layer and the second outer skin layer may have a load deflection temperature higher than the load deflection temperature of the resin material of the core layer. The coextruded sheet may have a load deflection temperature of 0.4 to 0.9 g / cm 3 density and satisfies the following formula (1).
[0036] 0.10≤(t1+t2) / T≤0.5···(1)
[0037] In formula (1), t1 represents the thickness of the first outer skin layer, t2 represents the thickness of the second outer skin layer, and T represents the thickness of the coextruded sheet.
[0038] In this way, by controlling the density of the co-extruded sheet, the load deflection temperature of the resin material of the outer skin layer and the thickness of the outer skin layer relative to the thickness of the co-extruded sheet, the expansion and cracking of the surface generated during thermal shaping such as vacuum forming can be further suppressed, and excellent lightness and mechanical strength can be obtained.
[0039] (Composition 2)
[0040] In addition, the coextruded sheet of the present invention may contain a polycarbonate resin. It may include a core layer formed of a foamed resin, a first skin layer formed of a non-foamed resin and laminated on one main surface of the core layer, and a second skin layer laminated on the other main surface of the core layer. The resin material of the first skin layer and the second skin layer may have a glass transition temperature higher than the glass transition temperature of the resin material of the core layer. The coextruded sheet may have a glass transition temperature of 0.4 to 0.9 g / cm 3 density and satisfies the following formula (1).
[0041] 0.10≤(t1+t2) / T≤0.5···(1)
[0042] In formula (1), t1 represents the thickness of the first outer skin layer, t2 represents the thickness of the second outer skin layer, and T represents the thickness of the coextruded sheet.
[0043] In this way, by controlling the density of the co-extruded sheet, the glass transition temperature of the resin material of the outer skin layer and the thickness of the outer skin layer relative to the thickness of the co-extruded sheet, the expansion and cracking of the surface generated during thermal shaping such as vacuum forming can be further suppressed, and excellent lightness and mechanical strength can be obtained.
[0044] (Composition 3)
[0045] In the coextruded sheet of configuration 1 or 2, when the coextruded sheet is heated for 30 minutes in a heating atmosphere at 250° C., the average thickness t3 of the coextruded sheet after heating can be 1.5 times or less relative to the average thickness t4 of the coextruded sheet before heating. This can suppress the deterioration of the design of the coextruded sheet during thermal shaping such as vacuum forming.
[0046] (Composition 4)
[0047] In the coextruded sheet of configuration 1 or 2, the coextruded sheet may include a bulge generated on the surface of the coextruded sheet when heated in a heating atmosphere at 250° C. for 30 minutes. The thickness t5 of the coextruded sheet including the bulge may be 1.5 times or less relative to the average thickness t4 of the coextruded sheet before heating. The coextruded sheet after heating may have a bulge per 100 cm 2 There is less than one bulging portion. This can suppress the deterioration of the design of the coextruded sheet during heat forming such as vacuum forming.
[0048] (Composition 5)
[0049] In the coextruded sheet of configuration 1 or 2, when the coextruded sheet is heated in a heating atmosphere at 250°C for 30 minutes, the average thickness t3 of the coextruded sheet after heating can be 1.5 times or less relative to the average thickness t4 of the coextruded sheet before heating. The coextruded sheet may include a bulge generated on the surface of the coextruded sheet due to heating when heated in a heating atmosphere at 250°C for 30 minutes. The thickness t5 of the coextruded sheet including the bulge can be 1.5 times or less relative to the average thickness t4 of the coextruded sheet before heating. The coextruded sheet after heating can have a bulge on its surface per 100 cm 2 There is less than one bulging portion. This can further suppress the deterioration of the design of the coextruded sheet during heat forming such as vacuum forming.
[0050] (Composition 6)
[0051] In the coextruded sheet of any one of configurations 1 to 5, when the coextruded sheet is heated at 200° C. for 30 minutes, the coextruded sheet may have a dimensional change rate of -5% to 0% in either the extrusion direction or the width direction orthogonal to the extrusion direction when viewed from above. This ensures the dimensional stability of the coextruded sheet during thermal shaping such as vacuum forming.
[0052] (Composition 7)
[0053] In the coextruded sheet of any one of configurations 1 to 6, the coextruded sheet may have a strength of 1.5 GPa·cm 3 Thereby, the weight of the coextruded sheet can be reduced and the mechanical strength can be improved.
[0054] (Composition 8)
[0055] In the coextruded sheet of any one of configurations 1 to 7, the polycarbonate resin contained in the first skin layer and the second skin layer may have a melt volume flow rate 1.0 to 5 times that of the polycarbonate resin contained in the core layer. This can suppress the unevenness of the cell size in the core layer.
[0056] (Composition 9)
[0057] In the coextruded sheet of any one of configurations 1 to 8, the resin material of the first skin layer and the second skin layer may have a deflection temperature under load of 5° C. or higher than the deflection temperature under load of the resin material of the core layer. This can effectively improve vacuum formability and more appropriately suppress deterioration in the design of the coextruded sheet during heat forming such as vacuum forming.
[0058] (Composition 10)
[0059] In the coextruded sheet of any one of configurations 2 to 8, the resin material of the first skin layer and the second skin layer may have a glass transition temperature of 5° C. or higher relative to the glass transition temperature of the resin material of the core layer. This can effectively improve vacuum formability and more appropriately suppress deterioration in the design of the coextruded sheet during thermal shaping such as vacuum forming.
[0060] (Composition 11)
[0061] In the coextruded sheet of any one of configurations 1 to 10, the core layer may have a foaming ratio of 1.6 to 3.3 times. This can suppress a decrease in mechanical strength while achieving weight reduction, and can suppress deterioration in the design of the coextruded sheet during heat forming such as vacuum forming.
[0062] Below, use Figure 1 to Figure 5 The embodiment of the co-extruded sheet 1 of the present disclosure is specifically described. It should be noted that the same reference numerals are used for the same and corresponding structures in the figures, and the same description is not repeated. It should be noted that, in order to make the description easy to understand, the structure is simplified or schematically shown, or a part of the constituent components is omitted in the referenced drawings below.
[0063] The coextruded sheet 1 is formed of a polycarbonate resin. The coextruded sheet 1 of the present embodiment has a sheet shape. The coextruded sheet 1 is manufactured by coextrusion molding of a molten polycarbonate resin. As long as the resin used in the present disclosure contains a polycarbonate resin, other engineering plastics may also be used. The coextruded sheet 1 of the present disclosure may contain engineering plastics or super engineering plastics. Engineering plastics are thermoplastic resins having a deflection temperature under load of more than 100°C. Engineering plastics, for example, in addition to polycarbonate resin (PC), also include modified polyphenylene ether (m-PPE), syndiotactic polystyrene (SPS), etc. Super engineering plastics are thermoplastic resins having a deflection temperature under load of more than 150°C. Super engineering plastics are, for example, polyphenylene sulfone (PPSU), polysulfone (PSU), polyarylate (PAR), polyetherimide (PEI), polyetheretherketone (PEEK), polyphenylene sulfide (PPS), polyethersulfone (PES), polyamide-imide (PAI), liquid crystal polymer (LCP), polyvinylidene fluoride (PVDF), etc. The resin that can be used in the coextruded sheet 1 of the present disclosure may include at least one selected from the group consisting of these engineering plastics and super engineering plastics. It should be noted that the resin material of the coextruded sheet 1 can be any engineering plastic that can be extruded. In addition, from the viewpoint of improving heat resistance, suppressing the reduction of the dimensional change rate caused by heating and the generation of bulging parts, the coextruded sheet 1 preferably includes a polycarbonate resin. Furthermore, from the viewpoint of improving the impact strength of the surface of the coextruded sheet 1, it is preferred to include a polycarbonate resin and a polycarbonate-polysiloxane copolymer.
[0064] In the resin material of the coextruded sheet 1, various additives may be contained to the extent that the thermal shaping and mechanical properties are not significantly affected. The types of additives are not particularly limited, and include, for example, bubble nucleating agents, crystallization nucleating agents, lubricants, surfactants, tension modifiers, shrinkage inhibitors, fluidity modifiers, impact modifiers, fillers, reinforcing agents, antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, plasticizers, lubricants, mold release agents, antistatic agents, colorants (pigments, dyes, etc.), surface effect additives, infrared absorbers, radiation stabilizers, anti-drip agents, and anti-aging agents. The amount of additives added can be appropriately selected within the range of not damaging the formation of bubbles, and the amount of additives used in the molding of conventional thermoplastic resins can be used.
[0065] The coextruded sheet 1 has a thickness of 0.4 to 0.9 g / cm 3 If the density of the coextruded sheet 1 is set to 0.4-0.9 g / cm 3 , it is possible to achieve both lightweighting and improved strength at the same time.
[0066] like Figure 1 As shown, the coextruded sheet 1 comprises a core layer 2, a skin layer 3 laminated on one main surface of the core layer 2, and a skin layer 4 laminated on the other main surface of the core layer 2. Figure 2 As shown, the coextruded sheet 1 has a thickness T of 1 to 5 mm. Within this thickness range, the coextruded sheet 1 can be suitably vacuum-formed while maintaining good vacuum formability.
[0067] The core layer 2 is formed of a foamed resin. The core layer 2 can be formed by foaming a molten polycarbonate resin. That is, the core layer 2 has a plurality of bubbles. In a cross-sectional view cut along the extrusion direction during extrusion molding and in the thickness direction, the plurality of bubbles have a roughly elliptical shape extending in the extrusion direction. Among the plurality of bubbles contained in the core layer 2, the bubbles contained near the center in the thickness direction of the core layer 2 have a bubble diameter larger than that of the bubbles 21 contained near the ends in the thickness direction of the core layer 2. The bubble diameters of the plurality of bubbles 21 gradually decrease as they move from the center in the thickness direction of the core layer 2 toward the ends in the thickness direction.
[0068] like Figure 2 As shown, the skin layer 3 is formed of a non-foamed resin. That is, the skin layer 3 is not foamed. The skin layer 3 is extruded from a die outlet in a non-foamed state by co-extrusion molding and is integrally laminated with the core layer 2. The skin layer 3 has a thickness t1.
[0069] The skin layer 3 can be made of a thermoplastic resin that can be well bonded to the core layer 2. More specifically, the resin material of the skin layer 3 is preferably the same resin material as the core layer 2. In addition, in order to strengthen the skin layer 3, the skin layer 3 can be composed of a reinforcing resin containing an inorganic filler. Through the composition of the skin layer 3, it is possible to achieve lightweight and improved strength while efficiently improving strength. Examples of inorganic fillers include glass fiber, carbon fiber, aramid fiber, talc, and mica.
[0070] The skin layer 4 has a thickness t2. The skin layer 4 is the same as the skin layer 3 except that it is laminated on the other main surface of the core layer 2. Therefore, a specific description of the skin layer 4 is omitted.
[0071] The thickness t1 of the skin layer 3 and the thickness t2 of the skin layer 4 are measured as follows. A cross section of the coextruded sheet 1 cut in the width direction and in the thickness direction is observed using a microscope. In the present disclosure, the microscope used is KEYENCE model VHX-6000. The magnification of the microscope can be a magnification of the bubble diameter that can confirm the interface between the skin layer 3 and the core layer 2 of the coextruded sheet 1. In the cross-sectional view of the coextruded sheet 1, among the bubbles present in large numbers, 15 bubbles close to the surface of the coextruded sheet 1 on each imaginary boundary line when the cross section 16 of the coextruded sheet 1 is divided equally in the width direction are selected, and the bubbles closest to the surface of the coextruded sheet 1 are confirmed. Draw an imaginary line that passes through the upper end of the closest bubble and is orthogonal to the thickness direction. Compared with the imaginary line, the inner side in the thickness direction is the core layer 2, and the outer side in the thickness direction is the skin layer 3. The boundary between the core layer 2 and the skin layer 4 is also defined in the same way, and the thickness t1 of the skin layer 3 and the thickness t2 of the skin layer 4 are measured. In order to make the thickness T of the coextruded sheet 1 as uniform as possible during coextrusion molding, the thickness t1 of the skin layer 3 and the thickness t2 of the skin layer 4 are each preferably 0.050 mm or more.
[0072] The total thickness of the skin layer obtained by adding the thickness t1 of the skin layer 3 and the thickness t2 of the skin layer 4 is preferably 0.10 to 0.5 with respect to the thickness T of the coextruded sheet 1. That is, the coextruded sheet 1 satisfies the following formula (1).
[0073] 0.10≤(t1+t2) / T≤0.5···(1)
[0074] If the thickness of the entire skin layer (t1+t2) is less than 0.10 relative to the thickness T of the coextruded sheet 1, it is difficult to obtain the reinforcing effect of the mechanical strength brought by the non-foamed resin of the skin layer, and the mechanical strength such as the specific bending modulus is reduced. On the other hand, if the thickness of the entire skin layer (t1+t2) is greater than 0.5 relative to the thickness T of the coextruded sheet 1, the density of the coextruded sheet 1 becomes larger. As a result, the coextruded sheet 1 will lose the lightness brought by foaming. The ratio of the thickness of the entire skin layer (t1+t2) to the thickness T of the coextruded sheet 1 is preferably in the range of 0.15 to 0.45, and more preferably in the range of 0.2 to 0.4. By making the ratio of the thickness of the entire skin layer (t1+t2) to the thickness T of the coextruded sheet 1 within this range, the specific bending modulus can be improved while achieving the lightness brought by the reduction in density. Furthermore, by setting the ratio of the overall skin layer thickness (t1+t2) to the coextruded sheet 1 thickness T to be in the range of 0.2 to 0.4, the core layer 2 thickness that makes bubble spots uniform can be ensured while improving secondary processability such as vacuum forming.
[0075] The resin material of the skin layer 3 and the skin layer 4 has a load deflection temperature higher than the load deflection temperature of the resin material of the core layer 2. That is, the load deflection temperature of the resin material of the skin layer 3 and the skin layer 4 is the same as the load deflection temperature of the resin material of the core layer 2, or higher than the load deflection temperature of the resin material of the core layer 2. As a result, the design of the molded product after vacuum forming can be further improved. Specifically, the resin material of the skin layer 3 and the skin layer 4 has a load deflection temperature higher than 5°C relative to the load deflection temperature of the resin material of the core layer 2. That is, the difference in load deflection temperature between the skin layer 3 and the core layer 2 is preferably 5°C or higher, and the difference in load deflection temperature between the skin layer 4 and the core layer 2 is preferably 5°C or higher. In this way, the resins of the skin layer 3, the skin layer 4, and the core layer 2 are selected so that the load deflection temperature of the resin material of the skin layer 3 and the skin layer 4 is higher than the load deflection temperature of the resin material of the core layer 2. As described above, in the coextruded sheet 1, since the core layer 2 is formed of a foamed resin, there may be a difference in thermal conductivity between the resin material of the skin layer 3 or the skin layer 4 and the resin of the core layer 2. When the coextruded sheet 1 is subjected to thermal shaping such as vacuum forming, if the load deflection temperature of the resin material of the skin layer 3 and the skin layer 4 of the coextruded sheet 1 is made lower than the load deflection temperature of the resin material of the core layer 2, the skin layer 3 and the skin layer 4 can be significantly softened compared to the core layer 2. Therefore, the skin layer 3 and the skin layer 4 may be peeled off from the core layer 2, resulting in poor appearance such as expansion and cracking, and the resin may not follow the mold uniformly. By making the load deflection temperature of the resin material of the skin layer 3 and the skin layer 4 higher than the load deflection temperature of the resin material of the core layer 2, it is possible to suppress significant softening of the skin layer 3 and the skin layer 4. Furthermore, when the coextruded sheet 1 is thermally formed into a molded product requiring deep drawing, by making the load deflection temperature of the resin material of the outer skin layer 3 and the outer skin layer 4 higher than the load deflection temperature of the resin material of the core layer 2 by 5°C or more, the corner trimming of the molded product can be appropriately performed, and the molded product can be finished to be sharper. The resin material of the outer skin layer 3 and the outer skin layer 4 can have a load deflection temperature of 60°C or less relative to the load deflection temperature of the resin material of the core layer 2. It should be noted that the upper limit of the load deflection temperature difference between the resin material of the outer skin layer 3 or the outer skin layer 4 and the resin material of the core layer 2 is not particularly limited.
[0076] The load deflection temperature is measured according to ISO075-2B with a load of 1.81 MPa for the resin materials of the outer skin layer 3 and the outer skin layer 4 and the resin material of the core layer 2. It should be noted that, in the resin material of the core layer 2, the load deflection temperature is set to the foamed molded body. More specifically, the outer skin layer 3 and the outer skin layer 4 in the co-extruded sheet 1 are peeled off from the core layer 2, and the load deflection temperature of each layer is measured. There is no particular limitation on the method of peeling the outer skin layer 3 and the outer skin layer 4 from the core layer 2. For example, the outer skin layer 3 and the outer skin layer 4 can be shaved out (surface alignment) using a contour processing tool (contour), or the outer skin layer 3 and the outer skin layer 4 can be cut out using an NC tool.
[0077] In this way, by controlling the density of the co-extruded sheet 1, the load deflection temperature of the resin material of the outer skin layer 3 and the outer skin layer 4, and the thickness (t1+t2) of the outer skin layer 3 and the outer skin layer 4 relative to the thickness T of the co-extruded sheet 1, it is possible to suppress surface expansion and cracking caused during thermal shaping such as vacuum forming, and to obtain excellent lightness and mechanical strength.
[0078] The resin material of the skin layer 3 and the skin layer 4 has a glass transition temperature higher than the glass transition temperature of the resin material of the core layer 2. That is, the glass transition temperature of the resin material of the skin layer 3 and the skin layer 4 is the same as the glass transition temperature of the resin material of the core layer 2, or higher than the glass transition temperature of the resin material of the core layer 2. As a result, the design of the molded product after vacuum forming can be further improved. The difference in glass transition temperature between the skin layer 3 and the core layer 2 is preferably 5°C or more, and the difference in glass transition temperature between the skin layer 4 and the core layer 2 is preferably 5°C or more. In this way, the resins of the skin layer 3, the skin layer 4, and the core layer 2 are selected so that the glass transition temperature of the resin material of the skin layer 3 and the skin layer 4 is higher than the glass transition temperature of the resin material of the core layer 2. As described above, since the core layer 2 of the coextruded sheet 1 is formed of a foamed resin, there may be a difference in thermal conductivity between the resin material of the skin layer 3 or the skin layer 4 and the resin of the core layer 2. When the coextruded sheet 1 is subjected to heat forming such as vacuum forming, if the glass transition temperature of the resin material of the skin layer 3 and the skin layer 4 of the coextruded sheet 1 is lower than the glass transition temperature of the resin material of the core layer 2, the skin layer 3 and the skin layer 4 can be significantly softened compared to the core layer 2. Therefore, the skin layer 3 and the skin layer 4 are separated from the core layer 2, and there is a possibility that the appearance is poor, such as swelling and cracking, and the resin does not follow the mold uniformly. By making the glass transition temperature of the resin material of the skin layer 3 and the skin layer 4 higher than the glass transition temperature of the resin material of the core layer 2, it is possible to suppress the significant softening of the skin layer 3 and the skin layer 4. Furthermore, when the coextruded sheet 1 is heat formed into a molded product requiring deep drawing, by making the glass transition temperature of the resin material of the skin layer 3 and the skin layer 4 higher than the glass transition temperature of the resin material of the core layer 2 by 5°C or more, the corner trimming of the molded product can be appropriately performed, and the molded product can be processed to be sharper. The resin material of the skin layer 3 and the skin layer 4 may have a glass transition temperature of 60°C or less relative to the glass transition temperature of the resin material of the core layer 2. It should be noted that the upper limit of the difference in glass transition temperature between the resin material of the skin layer 3 or the skin layer 4 and the resin material of the core layer 2 is not particularly limited.
[0079] The glass transition temperature is measured for the resin material of the outer skin layer 3 and the outer skin layer 4 and the resin material of the core layer 2 in accordance with JIS K-7121. It should be noted that the glass transition temperature of the foamed molded body is used as the resin material of the core layer 2. More specifically, the outer skin layer 3 and the outer skin layer 4 in the coextruded sheet 1 are peeled off from the core layer 2, and the glass transition temperature of each layer is measured. The method for peeling the outer skin layer 3 and the outer skin layer 4 from the core layer 2 is not particularly limited. For example, the outer skin layer 3 and the outer skin layer 4 can be cut out using a contour processing tool (surface alignment), or the outer skin layer 3 and the outer skin layer 4 can be cut out using an NC tool.
[0080] In this way, by controlling the density of the co-extruded sheet 1, the glass transition temperature of the resin material of the outer skin layer 3 and the outer skin layer 4, and the thickness (t1+t2) of the outer skin layer 3 and the outer skin layer 4 relative to the thickness T of the co-extruded sheet 1, it is possible to suppress surface expansion and cracking generated during thermal shaping such as vacuum forming, and to obtain excellent lightness and mechanical strength.
[0081] The melt volume flow rate (hereinafter referred to as MVR) of the polycarbonate resin contained in the outer skin layer 3 is the same as the MVR of the polycarbonate resin contained in the core layer 2, or higher than the MVR of the polycarbonate resin contained in the core layer 2. The MVR of the polycarbonate resin contained in the outer skin layer 3 is 1.0 to 5 times, preferably 1.5 to 3 times, the MVR of the polycarbonate resin contained in the core layer 2.
[0082] By making the MVR of the resin contained in the skin layer 3 equal to or higher than the MVR of the resin contained in the core layer 2, the temperature of the resin forming the skin layer 3 can be reduced as much as possible immediately after being discharged from the die outlet during extrusion molding. As a result, the viscosity of the skin layer 3 immediately after being discharged from the die outlet can be reduced, so that bulging or cracking of the surface of the skin layer 3 caused by the unevenness of the bubble size contained in the core layer 2 can be suppressed. That is, if the ratio of the MVR of the resin contained in the skin layer 3 is less than 1.0 times, it is difficult to reduce the resin temperature, and therefore it is difficult to suppress bulging or cracking of the surface of the skin layer 3. In addition, if the ratio of the MVR of the resin contained in the skin layer 3 is 1.5 times or more, it is easier to suppress the unevenness of the bubble size of the core layer 2 during extrusion molding, and the preheating time during vacuum molding can be shortened to improve productivity. On the other hand, when the ratio of the MVR of the resin contained in the skin layer 3 is greater than 5 times, if the resin forming the skin layer 3 is to be properly flowed in the mold during extrusion molding, the MVR of the resin forming the core layer 2 needs to be extremely reduced. In addition, if the ratio of the MVR of the resin contained in the skin layer 3 is 3 times or less, the bubble spots of the core layer 2 of the coextruded sheet 1 are easily uniform, and the secondary processability of the coextruded sheet 1 such as vacuum molding can be improved. Therefore, if the appropriate fluidity of the resin forming the core layer 2 and the skin layer 3 is ensured during extrusion molding, and the viscosity is controlled to suppress swelling or cracking of the surface of the skin layer 3, the MVR of the polycarbonate resin contained in the skin layer 3 can be 1.0 times to 5 times, preferably 1.5 times to 3 times, relative to the MVR of the polycarbonate resin contained in the core layer 2. This is also the same for the skin layer 4 and the core layer 2.
[0083] It should be noted that the MVR of the resin contained in the skin layer 3 and the core layer 2 is measured by a plastic flow characteristic test (according to JIS K7199, ISO 11443) using a capillary rheometer and a slit die rheometer. In the present disclosure, the capillary die length is set to 5 mm, the inner diameter is set to 1 mm, and the measurement temperature is set to 300° C. for measurement.
[0084] The core layer 2 has a foaming ratio of 1.6 to 3.3 times. By setting the foaming ratio of the core layer 2 to 1.6 times or more, lightweighting can be achieved. That is, if the foaming ratio of the core layer 2 is less than 1.6 times, it is difficult to fully obtain the lightweight effect. On the other hand, by setting the foaming ratio of the core layer 2 to 3.3 times or less, the reduction in mechanical strength caused by foaming can be suppressed. That is, if the foaming ratio of the core layer 2 is greater than 3.3 times, the mechanical strength may be reduced. In addition, by setting the foaming ratio of the core layer 2 to 1.6 to 3.3 times, the deterioration of the appearance design of the co-extruded sheet 1 during thermal shaping such as vacuum forming can be suppressed. For example, when the molded product after thermal shaping such as vacuum forming of the co-extruded sheet 1 is used as an inner wall material of a mobile tool such as an automobile, it can contribute to reducing environmental costs including increased energy consumption, and can contribute to the safety of the mobile tool. Furthermore, the appearance design of the interior of the mobile tool can be improved. The foaming ratio of the core layer 2 may be 1.6 times or more, preferably 1.7 times or more, more preferably 1.9 times or more, and may be 3.3 times or less, preferably 2.8 times or less, more preferably 2.3 times or less.
[0085] The expansion ratio of the core layer 2 is calculated by any of the following methods (1) to (3). That is, if at least one of the expansion ratios of the coextruded sheet 1 calculated by the following methods (1) to (3) is in the range of 1.6 to 3.3 times, it can contribute to the above-mentioned lightness, suppression of reduction in mechanical strength, and suppression of reduction in appearance design. Usually, the expansion ratios calculated by the methods (1) to (3) are approximate values.
[0086] (1) The expansion ratio of the core layer 2 can be calculated as follows. First, the coextruded sheet 1 is cut to obtain a sheet of an arbitrary size. The weight of the sheet is measured and the weight per unit area W (kg / m 2 The thickness (t1+t2) of the outer skin layer 3 and the outer skin layer 4 is measured in the same manner as the cross-sectional observation method using the above-mentioned microscope. Based on the density ρ1 (kg / m 3 ) and the thickness of the outer skin layer 3 and the outer skin layer 4, and calculate the weight per unit area W1 (kg / m 2 )<W1=ρ1×(t1+t2)> Next, calculate the weight W2 (kg / m 2). The thickness of the core layer {T-(t1+t2)} is measured using the cross-sectional observation method described above. The density of the core layer 2 is calculated from the weight and thickness of the core layer 2 as ρ2<ρ2=W2 / {T-(t1+t2)}>. The density of the resin material of the core layer 2 before foaming is ρ 2f Calculate the foaming ratio < foaming ratio = ρ 2f / ρ2>.
[0087] (2) The foaming ratio of the core layer 2 can also be calculated as follows. First, a high-resolution X-ray CT with a resolution of 1.5 μm or more (e.g., model "inspeXio SMX-225CTS" manufactured by Shimadzu Corporation) is used to obtain a three-dimensional image of the coextruded sheet 1. Next, in the three-dimensional image, the brightness of the extrusion direction of the coextruded sheet 1 is analyzed using image processing software (e.g., "Image J" manufactured by the National Institutes of Health of the United States). It should be noted that the image processing software is not limited as long as it can binarize the brightness of the three-dimensional image in black and white. Next, in the three-dimensional image, the brightness of the bubble wall between multiple bubbles, that is, the non-void area, is extracted. At this time, the threshold value for the binarization processing representing the brightness of the bubble wall is obtained based on the concentration histogram obtained by the Otsu method. Next, the average value of the brightness of the entire coextruded sheet 1 obtained by the above analysis is calculated. Finally, the brightness of the extracted bubble wall is divided by the average value of the brightness of the entire coextruded sheet 1. In this way, the foaming ratio can also be calculated.
[0088] (3) The expansion ratio of the core layer 2 can also be calculated as follows. First, the skin layer 3 and the outer skin layer 4 are scraped off from the coextruded sheet 1 to extract the core layer 2. The method for scraping off the skin layer 3 and the outer skin layer 4 is cutting or grinding, etc., but is not particularly limited. Next, for the resin material of the core layer 2, the melting point of the resin material of the core layer 2 is measured by differential scanning calorimetry (DSC). The device used in DSC is not particularly limited, for example, it is DSC8230 manufactured by Rigaku Corporation. The core layer 2 is melted in an electric furnace set to a temperature 10°C higher than the measured melting point temperature. At this time, the melting time depends on the resin material of the core layer 2 and is 1 hour. The molten resin is taken out from the electric furnace, and the density of the molten resin is measured by the water displacement method. The density of the core layer 2 extracted by the above-mentioned scraping is also measured by the water displacement method. The value obtained by dividing the density of the molten resin by the density of the core layer 2 is used as the expansion ratio. In this way, the expansion ratio can also be calculated.
[0089] It should be noted that the core layer 2 of the present disclosure is preferably foamed using a physical foaming agent such as nitrogen or carbon dioxide with a relatively low pressure as disclosed in the above-mentioned patent document 1, wherein nitrogen is more preferred. As a result, the pressure of the physical foaming agent can be set to a relatively low 1 to 6 MPa, and a plurality of fine bubbles can be formed. As a result, it is possible to more reliably suppress expansion during high temperature and heating during vacuum forming. The average bubble diameter of the bubbles can be greater than 0.1 mm, can be less than 1.0 mm, and is preferably less than 0.3 mm.
[0090] The coextruded sheet 1 is formed into various shapes by vacuum forming. In vacuum forming, usually, after the coextruded sheet 1 is heated to about 200°C and begins to drape, it is adhered to a mold or the like and formed by vacuum suction. That is, the coextruded sheet 1 preferably has a small deformation amount (dimensional change rate before and after heating) relative to the heating temperature during vacuum forming. When the coextruded sheet is heated in an atmosphere of 200°C for 30 minutes, the coextruded sheet 1 has a dimensional change rate of -5% to 0% in the extrusion direction. In addition, the coextruded sheet 1 has a dimensional change rate of -5% to 0% in the width direction. That is, the coextruded sheet 1 has a dimensional change rate of -5% to 0% in either the extrusion direction or the width direction. Alternatively, the coextruded sheet 1 has a dimensional change rate of -5% to 0% in both the extrusion direction and the width direction. The width direction refers to a direction orthogonal to the above-mentioned extrusion direction when viewed from above. As a result, the coextruded sheet 1 has excellent dimensional stability before and after heating.
[0091] The dimensional change rate in the extrusion direction can be calculated according to the following formula.
[0092] Dimensional change rate in extrusion direction (%) = {(distance between marking lines in extrusion direction after heating - distance between marking lines in extrusion direction before heating) / distance between marking lines in extrusion direction before heating} × 100
[0093] On the other hand, the dimensional change rate in the width direction can be calculated according to the following formula.
[0094] Dimension change rate in width direction (%) = {(distance between marking lines in width direction after heating - distance between marking lines in width direction before heating / distance between marking lines in width direction before heating)} × 100
[0095] Coextruded sheet 1 has a viscosity of 1.5 GPa·cm 3 / g or more specific bending modulus. Specific bending modulus refers to the value obtained by dividing the bending modulus of the coextruded sheet 1 by the density of the coextruded sheet 1. That is, it can be said that the larger the specific bending modulus, the better the lightness and mechanical strength. The bending modulus is measured by a three-point bending test (according to ISO178 or JIS7171). At this time, the bending modulus is measured in the atmosphere. The test speed is 10mm / min. In addition, the coextruded sheet 1 preferably has 2.0GPa·cm 3 / g or more. Thus, since the polycarbonate resin has a higher specific flexural modulus than that of a non-foamed polycarbonate resin, excellent lightness and mechanical strength can be more effectively obtained.
[0096] The coextruded sheet 1 is thermally formed into a desired shape mainly by vacuum forming or the like. If the coextruded sheet is heated, expansion (bulging portion) may occur on the sheet surface, and the appearance design of the sheet surface may be deteriorated. Therefore, it is preferable to suppress the generation of bulging portions of the coextruded sheet 1. Figure 3 As shown, when the coextruded sheet 1 is heated at 250°C for 30 minutes, the average thickness t3 of the coextruded sheet 1 after heating is less than 1.5 times the average thickness t4 of the coextruded sheet before heating. Figure 3 The dotted line S in the figure is the surface of the coextruded sheet 1 before heating. That is, the coextruded sheet 1 can suppress the generation of the bulge caused by heating, and can reduce the thickness change between before and after heating. Thus, the coextruded sheet 1 can improve the appearance design during thermal shaping such as vacuum forming.
[0097] In addition, if Figure 4 As shown, the thickness t5 of the coextruded sheet including the bulging portion 11 is relative to Figure 3 The average thickness t4 of the coextruded sheet before heating is 1.5 times or less. 2 There is less than one bulging portion 11. That is, according to the coextruded sheet 1, the height of the bulging portion 11 generated on the surface due to heating can be reduced, and the number of bulging portions 11 generated can be suppressed. As a result, the coextruded sheet 1 can achieve an improvement in the appearance design during thermal shaping such as vacuum forming. The thermally shaped body of the coextruded sheet is used for applications that particularly require appearance design, such as containers such as signs, suitcases, and interior and exterior materials for vehicles such as automobiles. Therefore, undesirable conditions such as expansion in the thermally shaped object are not expected in the listed applications. Therefore, the expansion of the coextruded sheet 1 during heating is suppressed as much as possible, and specifically, the bulging portion 11 is preferably less than one.
[0098] The co-extruded sheet 1 may contain a plurality of flaky fillers. The flaky fillers are, for example, inorganic fillers such as talc, calcium carbonate, mica, clay, boron nitride, wollastonite, potassium titanate, and glass flakes. The flaky fillers may be subjected to surface treatments such as silane coupling agents, titanate coupling agents, phosphate coupling agents, and fatty acid coupling agents. The flaky fillers have an aspect ratio of more than 5. The aspect ratio is calculated by dividing the average particle size of the flaky filler by the average thickness (average particle size / average thickness). If the aspect ratio of the flaky filler is too small, it is difficult to exert excellent surface smoothness. Therefore, the aspect ratio of the flaky filler is preferably more than 10, more preferably more than 30. However, if the aspect ratio is too large, it is not easy to control the flow rate of the mixed molten resin inside the mold in the manufacturing process described later, and the surface smoothness may deteriorate. In addition, the viscosity of the mixed molten resin during extrusion molding increases, and thermal degradation of the thermoplastic resin may occur due to the heat generated in the extrusion molding device described later. Therefore, the aspect ratio of the flaky filler may be less than 50. The specific surface area of the flaky filler is preferably 5 to 20 m 2 If the specific surface area of the flaky filler is too small, it is difficult to exhibit surface smoothness due to the sliding of the flaky filler on the surface, and if the specific surface area is too large, the resistance of the flaky filler in the molten resin becomes large, resulting in difficulty in properly orienting the flaky filler.
[0099] The core layer 2 may contain a flaky filler oriented approximately parallel to the boundary surface between the core layer 2 and the skin layer 3 in the vicinity of the boundary with the skin layer 3. The vicinity is an area in the thickness direction of the core layer 2, which is located from the boundary surface between the core layer 2 and the skin layer 3 to a thickness of 5% relative to the thickness of the core layer. In addition, the bubbles contained in the core layer 2 are in a shape extending along the extrusion direction during extrusion molding. The flaky filler is also oriented approximately parallel to the bubble wall of the bubble extending in the extension direction, so that the strength of the bubble wall can be improved. As a result, the rupture of the coextruded sheet 1 along the extrusion direction can be suppressed. It should be noted that the flaky filler is approximately parallel, which means that in the cross section of the coextruded sheet 1 cut along the extrusion direction during extrusion molding and in the thickness direction, the flaky filler has a slope of 0° or more and less than 5° relative to the boundary surface between the core layer 2 and the skin layer 3. In other words, it refers to the state in which the surface (main surface) of the flaky filler is relatively parallel to the boundary surface between the core layer 2 and the skin layer 3. The same is true for the flaky filler oriented in the core layer 2 near the boundary between the core layer 2 and the skin layer 4 .
[0100] The orientation state of the multiple flaky fillers contained in the region near the boundary between the core layer 2 and the outer skin layer 3 is calculated as follows. First, in a cross section in the thickness direction along the extrusion direction during extrusion molding, 50 150×150μm electron microscope photos are taken at equal intervals from the front end to the rear end in the extrusion direction of the nearby region and at the center of the thickness direction of the nearby region. Among all the flaky fillers contained in these 50 electron microscope photos, flaky fillers oriented approximately parallel to the boundary surface between the core layer 2 and the outer skin layer 3 are confirmed. Thus, the proportion of flaky fillers oriented approximately parallel to the multiple flaky fillers contained in the nearby region is calculated.
[0101] The core layer 2 may contain a flaky filler oriented at an angle of 5° to 90° relative to the surface of the coextruded sheet 1 in the central region in the thickness direction of the core layer 2. The central region refers to a region with a thickness of 25% from the center in the thickness direction toward the boundary surface between the core layer 2 and the outer skin layer 3 when the thickness of the core layer 2 is set to 100%. Preferably, more than 40% of the flaky fillers contained in the central region are oriented at an angle of 5° to 90° relative to the surface S of the coextruded sheet 1. Thus, the moldability of the coextruded sheet 1 can be improved. More preferably, more than 60%, and further preferably more than 80% of the flaky fillers are oriented at an angle of 5° to 90° relative to the surface. Thus, the moldability of the coextruded sheet 1 can be further improved. The bubbles contained in the central region of the core layer 2 tend to become larger than the above-mentioned nearby regions during extrusion molding. This is because the central region is difficult to cool after extrusion compared to the nearby regions. If the bubbles become too large, it becomes the main cause of the breakage of the coextruded sheet 1. As described above, by arranging the flaky filler in an inclined state and randomly between bubbles in the central region, it is possible to suppress the growth of bubbles in all directions. Thus, the strength of the coextruded sheet 1 or the strength during molding, i.e., the moldability, can be improved. As a result, when the coextruded sheet 1 is vacuum-molded into a material to produce a foamed resin molded product, the bubbles contained in the coextruded sheet 1 can be suppressed from breaking or the coextruded sheet 1 can be suppressed from being damaged.
[0102] The orientation state of the multiple flaky fillers contained in the central area of the core layer 2 can be calculated as follows. First, 50 microscope photographs are taken at equal intervals at the center of the thickness direction of the core layer 2, as in the case of the nearby area. Among all the flaky fillers contained in these 50 electron microscope photographs, flaky fillers that are oriented at an angle of 5° to 90° relative to the surface of the coextruded sheet 1 are confirmed. Thus, the proportion of flaky fillers that are oriented at an angle of 5° to 90° relative to the surface of the coextruded sheet 1 among the multiple flaky fillers contained in the central area is calculated.
[0103] Next, the manufacturing method of the co-extruded sheet 1 is described (not shown). First, resin particles as a resin material are added to the screw barrel of the main extruder. The resin material is a polycarbonate resin. The resin particles are heated in the screw barrel to generate a molten resin. Next, a foaming agent is injected into the molten resin from a foaming agent injection bottle installed in the screw barrel of the main extruder. The foaming agent is dissolved in the molten resin through the above-mentioned screw barrel, kneaded and evenly dispersed. In this way, a mixed molten resin is generated. The mixed molten resin is discharged from the die outlet to form a core layer 2. At the same time, resin particles as a resin material are respectively added to the screw barrels of the two auxiliary extruders, heated and melted, thereby generating two molten resins. One of the two molten resins is discharged from the die outlet to form an outer skin layer 3, and the other is discharged from the die outlet to form an outer skin layer 4. The mixed molten resin and the two molten resins are merged in a die from their respective extruders, and are discharged from the die outlet in a manner that the outer skin layer 3 is laminated on one main surface of the core layer 2 and the outer skin layer 4 is laminated on the other main surface of the core layer 2. The mixed molten resin foams when it is extruded from the die outlet into the atmosphere. In this way, a coextruded sheet 1 is manufactured. It should be noted that the foaming method is a physical foaming method using an inert gas such as nitrogen and carbon dioxide as a foaming agent. The coextruded sheet 1 extruded in this way is transported to a cutting machine by a tractor. The cutting machine cuts the coextruded sheet 1 into a desired shape.
[0104] The coextruded sheet 1 thus manufactured can be formed into a desired shape by vacuum forming or the like and used for the following purposes. For example, it is a wide range of products and parts such as signs or mobile tool materials such as automobile exterior materials that require strength, products and parts that require heat resistance such as trays for heat-generating components used in manufacturing processes with heating processes, or products and parts that require lightness. The coextruded sheet 1 contains polycarbonate resin and is foamed by coextrusion molding, so it is suitable as a material for molding these products and parts.
[0105] Furthermore, if Figure 5As shown, the coextruded sheet 1 may have a decorative film 5. The decorative film 5 is laminated on the outer surface of at least one of the skin layer 3 and the skin layer 4. The outer surface of the skin layer 3 refers to the surface of the skin layer 3 on the opposite side of the surface opposite to the core layer 2. The outer surface of the skin layer 4 is the same. By selecting the desired decorative film 5 from a plurality of decorative films 5 with various designs, it is possible to give a design suitable for the use of the molded product formed by vacuum forming the coextruded sheet 1. As the decorative film 5, there is no particular limitation, for example, a colored film, a film with any pattern printed on the surface, a film with leather grain, wood grain, stone grain or carbon fiber style, or a decorative film with a metallic surface gloss given by vapor deposition processing can be used. The material of the decorative film 5 is, for example, PC, PMMA, PC / PMMA alloy, ABS, AES, vinyl chloride, copolymerized PET, etc. The coextruded sheet 1 can be composed of three layers, namely the core layer 2, the skin layer 3 and the skin layer 4, or it can be composed of a decorative film 5 laminated on at least one of the skin layer 3 and the skin layer 4.
[0106] Products and parts made of the coextruded sheet 1 can reduce the amount of resin used. As a result, the coextruded sheet 1 of the present embodiment can contribute to the improvement of resource utilization efficiency, the reduction of transportation burden, the reduction of energy usage and the reduction of CO2 emissions. By providing the coextruded sheet 1 to society, it is possible to contribute to the achievement of Goal 7 (providing clean energy for everyone), Goal 9 (creating a foundation for industrial and technological innovation) and Goal 11 (creating sustainable towns) among the 17 goals of the Sustainable Development Goals (SDGs) formulated by the United Nations.
[0107] As mentioned above, although embodiment was described, this disclosure is not limited to the said embodiment, Various changes are possible as long as they do not deviate from the summary.
[0108] (Example)
[0109] As shown in Tables 1 and 2 below, test pieces of Examples 1 to 22 and Comparative Examples 1 to 14 were prepared, and the specific bending elastic modulus and the presence or absence of damage in the Charpy impact test, the expansion test of the test piece when heated at 250° C. for 30 minutes, and the appearance evaluation of the vacuum formed product (vacuum forming evaluation) were evaluated. The resin materials used for these test pieces were polycarbonate resins. It should be noted that the present disclosure is not limited to these embodiments.
[0110] [Table 1]
[0111]
[0112] [Table 2]
[0113]
[0114] (Example 1)
[0115] The test piece of Example 1 is made by co-extrusion molding as follows. First, a polycarbonate resin is added to the screw barrel of the main extruder, and shear kneading is performed while heating at 270°C. Then, a foaming agent N2 is injected at a pressure of 4 MPa. The polycarbonate resin and the foaming agent are heated and melted at 215°C, and the temperature at the die outlet is set to 215°C to obtain a core layer. At the same time, a polycarbonate resin is added to the screw barrel of the secondary extruder, and shear kneading is performed while heating at 255°C, and the temperature at the die outlet is set to 215°C to obtain two outer skin layers. These core layers and outer skin layers are merged and stacked in the die, and discharged from the die outlet. In this way, a test piece of Example 1 is obtained in which an outer skin layer formed by a non-foamed resin is stacked on the two main surfaces of the core layer formed by the foamed resin. It should be noted that the die outlet gap was set so that the thickness T of the test piece of Example 1 became the value shown in Table 1, and the pulling speed was set to 0.7 m / min, and the test piece of Example 1 was co-extruded. The deflection temperature under load of each of the skin layer and the core layer was measured using molded products of each of the skin layer and the core layer extruded into a single layer at the same temperature using a main extruder before co-extrusion lamination. It should be noted that polycarbonate resins with different deflection temperatures under load were selected from various polycarbonate resins so that the deflection temperatures under load of the skin layer and the core layer were different.
[0116] (Examples 2 to 11)
[0117] The test pieces of Examples 2 to 11 were prepared by setting the die outlet gap, the discharge flow rate of the main extruder and the sub-extruder, and the pulling speed so that the thickness T of each piece became the value shown in Table 1, and were prepared by the same method as the test piece of Example 1. That is, the test pieces of Examples 1 to 11 were different in thickness and load deflection temperature of the resin material of the outer skin layer and the core layer.
[0118] (Example 12)
[0119] The test piece of Example 12 is made by co-extrusion molding as follows. First, a polycarbonate resin is added to the screw barrel of the main extruder, and shear kneading is performed while heating at 270°C. Then, a foaming agent N2 is injected at a pressure of 4 MPa. The polycarbonate resin and the foaming agent are heated and melted at 215°C, and the temperature at the die outlet is set to 215°C to obtain a core layer. At the same time, a polycarbonate resin is added to the screw barrel of the secondary extruder, and shear kneading is performed while heating at 255°C, and the temperature at the die outlet is set to 215°C to obtain two outer skin layers. These core layers and outer skin layers are merged and stacked in the mold and discharged from the outlet of the mold. In this way, a test piece of Example 12 is obtained in which an outer skin layer formed by a non-foamed resin is stacked on the two main surfaces of the core layer formed by the foamed resin. It should be noted that the die outlet gap was set so that the thickness T of the test piece of Example 1 became the value shown in Table 2, and the pulling speed was set to 0.7 m / min, and the test piece of Example 12 was co-extruded. The glass transition temperature of each of the skin layer and the core layer was measured using each molded product of the skin layer and the core layer extruded into a single layer at the same temperature using a main extruder before co-extrusion lamination. It should be noted that polycarbonate resins with different glass transition temperatures were selected from various polycarbonate resins so that the glass transition temperatures of the skin layer and the core layer were different.
[0120] (Examples 13 to 22)
[0121] The test pieces of Examples 13 to 22 were prepared by setting the die outlet gap, the discharge flow rate of the main extruder and the sub-extruder, and the pulling speed so that the thickness T of each piece became the value shown in Table 2, and the same method as the test piece of Example 12 was used. That is, the test pieces of Examples 12 to 22 were different in thickness and the glass transition temperature of the resin material of the outer skin layer and the core layer.
[0122] (Comparative Example 1)
[0123] Each test piece of Comparative Example 1 was made by the co-extrusion molding method as follows. First, a polycarbonate resin was added to the screw barrel of the main extruder, and shear kneading was performed while heating at 270°C. Then, the blowing agent isopentane gas was injected in such a manner that the content reached 0.53 mol / kg of resin. The polycarbonate resin and the blowing agent were heated and melted at 215°C, and the temperature at the die outlet was set to 215°C to obtain a core layer. At the same time, a polycarbonate resin was added to the screw barrels of each of the two auxiliary extruders, and shear kneading was performed while heating at 255°C, and the temperature at the die outlet was set to 215°C to obtain two outer skin layers. These core layers and outer skin layers were merged in the die and stacked, and discharged from the die outlet. In this way, each test piece of Comparative Example 1 was obtained in which an outer skin layer formed by a non-foamed resin was stacked on the two main surfaces of the core layer formed by the foamed resin. The test piece of Comparative Example 1 was co-extruded by setting the die outlet gap so that the thickness T of the test piece of Comparative Example 1 would be the value shown in Table 1 and setting the pulling speed to 6.5 m / min.
[0124] (Comparative Examples 2 and 8)
[0125] The test pieces of Comparative Examples 2 and 8 were made using an extrusion lamination method in the following manner. First, a polycarbonate resin was added to the screw barrel of the main extruder, and shear kneading was performed while heating at 270°C. Then, a foaming agent isopentane gas was injected in such a manner that the content was 0.53 mol relative to 1 kg of the polycarbonate resin added. The polycarbonate resin and the foaming agent were heated and melted at 200°C, and the temperature at the die outlet was set to 200°C to obtain a core layer. The die outlet gap was set in such a manner that the thickness T of the test piece of Comparative Example 2 became the value shown in Table 1, and the pulling speed was set to 6.5 m / min, and the core layer was extruded. Next, in a molten state of the discharged core layer, two pre-made outer skin layers formed of polycarbonate resin were respectively adhered to the two main surfaces of the core layer and stacked.
[0126] (Comparative Examples 3 and 9)
[0127] The test pieces of Comparative Examples 3 and 9 were produced by laminating the core layer and the skin layer by thermal compression bonding. First, the core layer was obtained in the same manner as the test piece of Comparative Example 2. Next, two pre-made skin layers made of polycarbonate resin were laminated on both main surfaces of the cooled and solidified core layer by thermal compression bonding.
[0128] (Comparative Examples 4, 5, 7, 10, 11 and 14)
[0129] The test pieces of Comparative Examples 4, 5, 7, 10, 11 and 15 were prepared by setting the die outlet gap, the discharge flow rate of the main extruder and the sub-extruder, and the pulling speed so that the thickness T of each piece becomes the value shown in Table 1, and using the same method as the test piece of Example 1.
[0130] (Comparative Examples 6 and 13)
[0131] The test pieces of Comparative Examples 6 and 13 were made by injection molding. A polycarbonate resin was put into the screw barrel of the injection molding machine, and shear kneading was performed while heating at 270°C. Then, nitrogen gas, a foaming agent, was injected at a pressure of 8 MPa, and the polycarbonate resin injected with the foaming agent was filled into the mold. Then, the pressure of the mold was released by the core back method to obtain the test piece. It should be noted that the mold was designed in such a way that the thickness of the test piece was 3 mm.
[0132] The density of the test piece shown in Table 1 is calculated as follows. Cut the sheet-like test piece in the extrusion direction with a size of 400 mm. After dividing the cross section of the test piece in the width direction into 11 equal parts in the width direction, remove the ends and measure the thickness at 10 locations at equal intervals, and take the arithmetic mean of these thicknesses as the average thickness of the test piece. The length of each side of the test piece in the width direction and the extrusion direction is measured using a ruler, and the volume of the test piece is calculated from the length of each side and the average thickness. In addition, the weight of the test piece is measured using an electronic balance, and the weight of the test piece is divided by the volume to obtain the density of the test piece.
[0133] The dimensional change rate shown in Table 1 is calculated as follows. First, a sample piece cut into a size of 120 mm × 120 mm is obtained from a sheet-like test piece. At this time, the sample piece is collected from the central part and both ends relative to the total width of the test piece. The central part refers to the part located at 1 / 2 of the length of the total width of the test piece, and the two ends refer to the part 50 mm away from the end of the total width of the test piece. Marks for the extrusion direction and the width direction are marked on each sample piece, and then, marks for measuring the distance between the markings in the extrusion direction and the width direction are marked in the center of each sample piece. Use a scale or metal ruler that can measure a minimum of 0.5 mm to measure the distance between the markings in the extrusion direction and the width direction. Then, a metal container with a PTFE (polytetrafluoroethylene) sheet on the inner bottom surface is placed in a dryer, and the temperature of the dryer is adjusted so that the temperature of the metal container becomes 200 ± 2 ° C. The sample piece is placed in a metal container and heated for 30 minutes. After the heating treatment is completed, the sample piece is taken out from the metal container, cooled to room temperature, and the distance between the markings in the extrusion direction and the width direction is measured. Then, the dimensional change rate was calculated using the above mathematical formula. It should be noted that, in all test pieces, the absolute value of the dimensional change rate in the extrusion direction was greater than the dimensional change rate in the width direction, so the dimensional change rate in the extrusion direction is shown in Table 1. That is, the dimensional change rate in the width direction is smaller than the dimensional change rate in the extrusion direction. Therefore, before and after heating, the dimensions in the width direction are more stable than those in the extrusion direction.
[0134] The thickness T and specific bending modulus of the test pieces shown in Table 1 were measured by the above-mentioned measuring methods. The MVR ratio shown in Table 1 is the ratio of the MVR of the polycarbonate resin contained in the skin layer to the polycarbonate resin contained in the core layer, and was measured by the above-mentioned measuring method.
[0135] In Table 1, "whether or not the test piece is damaged" indicates whether or not each test piece is damaged by the impact test. In the Charpy impact test (according to ISO179-1, JIS7111-1), for each test piece, a flatwise vertical test is performed without a notch, and a 4J pendulum is used to evaluate whether or not the test piece is damaged. The state in which the test piece is not completely damaged, the hinge is damaged, or the state in which the test piece is partially damaged but only bent is evaluated as "A" for not being damaged, and the state other than this is regarded as being damaged and evaluated as "B".
[0136] In Table 1, "sheet expansion / bulging portion" indicates the surface expansion of each sheet-shaped test piece after heating. Surface expansion is the bulging portion mentioned above. For each test piece, evaluate whether the sheet expands after heating at a temperature of 250°C for 30 minutes. The specific method is described below. Calculate the average thickness of the test piece before heating. Use a micrometer to observe the cross section of the test piece. After dividing the cross section of the test piece into 11 equal parts in the width direction, remove the end and measure the thickness at 10 locations at equal intervals, and take the arithmetic mean of these thicknesses as the average thickness. The average thickness of the test piece after heating is calculated in the same way as the test piece before heating. In addition, visually confirm the test piece after heating to determine whether there is a bulging portion compared to the surface of the test piece before heating. When a bulging portion is visually confirmed, use a microscope to observe the cross section including the bulging portion, and measure the thickness t5 of the test piece including the bulging portion (refer to Figure 4). When the average thickness t3 of the test piece after heating is greater than 1.5 times the average thickness t4 of the test piece before heating, and the thickness t5 of the test piece including the bulging part is greater than 1.5 times the average thickness t4 of the test piece before heating, it is evaluated as the presence of surface expansion, and the case where there are more than one bulging part is evaluated as "C", the case where there are less than one bulging part is evaluated as "B", and the other cases are evaluated as "A". The heating method of the test piece is described below. First, the test piece is cut into a size of 100mm×100mm to obtain a sample piece. At this time, the sample piece is collected from the center and both ends relative to the total width of the test piece. The center refers to the part located at 1 / 2 of the length of the total width of the piece, and the two ends refer to the part 50mm away from the end of the total width of the piece. A metal container with a PTFE (polytetrafluoroethylene) sheet on the inner bottom is placed in an electric furnace, and the temperature of the electric furnace is adjusted so that the temperature of the metal container becomes 250±2℃. Each cut test piece is placed in a metal container and heated for 30 minutes. After the heat treatment was completed, the test piece was taken out from the metal container, cooled to room temperature, and the surface condition of the test piece was visually checked.
[0137] (Evaluation method of vacuum formability)
[0138] First, prepare a vacuum forming mold. Figure 6 As shown, the vacuum forming mold 100 has a recessed portion 101 recessed from its upper surface, and the recess 101 has a substantially rectangular shape when viewed from above. The corners of the recess 101 are chamfered with a radius of curvature of 15 mm, the distance between the relatively short sides of the substantially rectangular shape is 200 mm, the distance between the relatively long sides is 80 mm, and the depth of the recess 301 is 30 mm. The test pieces of Examples 1 to 11 and Comparative Examples 1 to 7 were vacuum formed using the vacuum forming mold. After heating the piece for 120 seconds with a heater at 250°C on the upper surface and 350°C on the lower surface, the piece was shaped using the vacuum forming mold 100. It should be noted that as a vacuum forming device, the "BVF-0710-W model" manufactured by Wakisaka Engineering Co., Ltd. was used. After vacuum forming, at the above-mentioned corners, the outer skin layer is separated from the core layer and the outer skin layer expands or the core layer cracks. Such a situation is regarded as poor vacuum formability and is evaluated as "C". The situation where the core layer does not crack but the bubble diameter of the core layer after vacuum forming is greater than 2 mm is regarded as good vacuum formability and is evaluated as "B". The situation where the core layer does not crack and the bubble diameter does not change significantly is regarded as better vacuum formability and is evaluated as "A".
[0139] (Test results)
[0140] Regarding the ratio of the thickness of the entire outer skin layer (t1+t2) to the thickness T of the coextruded sheet, in Examples 1 to 22, when the thickness ratio {(t1+t2) / T} was 0.10 to 0.5, the "specific bending modulus", "sheet expansion / bulging portion" and "presence of damage" were all evaluated as "B" or above. In particular, when the thickness ratio was 0.20 to 0.40 and the density of the test piece was 0.4 to 0.9 g / cm 3 In the case of , the evaluation "A" was obtained in "Specific bending elastic modulus" and "Presence of damage". That is, by controlling the thickness ratio {(t1+t2) / T} of the outer skin layer 3 and the core layer 2 of the coextruded sheet to 0.20-0.40 and the density to 0.4-0.9 g / cm 3 , which can achieve lightness and improvement of mechanical strength.
[0141] Next, regarding the MVR ratio of the resin of the outer skin layer 3 and the core layer 2 of the test piece, when the MVR ratio is 1 to 5 times in Examples 1 to 22, the "specific bending elastic modulus", "sheet expansion / bulging portion" and "presence of damage" all received an evaluation of "B" or above. In particular, when the MVR ratio is 1.5 to 3 times, an evaluation of "A" is obtained in both "sheet expansion / bulging portion" and "presence of damage". That is, when the MVR ratio of the resin contained in the outer skin layer 3 is 1.5 to 3 times, the bubble spots of the core layer 2 of the co-extruded sheet 1 tend to become uniform, and the secondary processability of the co-extruded sheet 1 such as vacuum forming can be improved. Furthermore, Examples 4, 5, 15 and 16 all received an evaluation of "A" in "specific bending elastic modulus", "sheet expansion / bulging portion" and "presence of damage". That is, the thickness ratio is preferably set to 0.20 or more and 0.40 or less, and the density of the test piece (sheet) is preferably set to 0.6 g / cm 3 Above 0.8g / cm 3 Hereinafter, the MVR ratio is preferably set to 1.7 times or more and 2.7 times or less.
[0142] Next, regarding the evaluation of the vacuum-formed products, in Examples 1 to 11, when the load deflection temperature of the resin material of the outer skin layer is higher than the load deflection temperature of the resin material of the core layer, the evaluation of the vacuum-formed products is evaluated as "A" or "B". In Examples 5 and 6, when the temperature difference between the load deflection temperature of the resin material of the outer skin layer and the load deflection temperature of the resin material of the core layer is equal to or less than 5°C, the evaluation of "B" is obtained. Therefore, by making the load deflection temperature of the outer skin layer resin higher than the load deflection temperature of the core layer resin, especially by making the temperature difference between the load deflection temperature of the resin material of the outer skin layer and the load deflection temperature of the resin material of the core layer be 5°C or more, the vacuum formability of heat-formed products such as vacuum-formed products can be improved, and the appearance design can be further improved.
[0143] In addition, regarding the evaluation of the vacuum-formed product, in Examples 12 to 22, when the glass transition temperature of the resin material of the outer skin layer is higher than the glass transition temperature of the resin material of the core layer, the evaluation of the vacuum-formed product is evaluated as "A" or "B". In Examples 16 and 17, when the temperature difference between the glass transition temperature of the resin material of the outer skin layer and the glass transition temperature of the resin material of the core layer is equal to or lower than 5°C, the evaluation of "B" is obtained. Therefore, by making the glass transition temperature of the outer skin layer resin higher than the glass transition temperature of the core layer resin, especially by making the temperature difference between the glass transition temperature of the resin material of the outer skin layer and the glass transition temperature of the resin material of the core layer 5°C or more, the vacuum formability of heat-formed products such as vacuum-formed products can be improved, and the appearance design can be further improved.
[0144] Comparative Examples 1 to 3 and 8 to 10 are low-density polycarbonate laminated resin sheets using isopentane gas as a blowing agent. The density of the test pieces of these Comparative Examples 1 to 3 and 8 to 10 is 0.1 to 0.11, which is less than 0.4. In addition, in the test pieces of Comparative Examples 1 to 3, the ratio of the thickness (t1+t2) of the outer skin layer to the thickness T of the test piece is less than 0.10.
[0145] The test pieces of Comparative Examples 1 to 3 and 8 to 10 use organic volatile isopentane gas as a foaming agent, so that the foaming ratio of the test pieces becomes larger. Therefore, on the surface of the test piece after extrusion foam molding, the unevenness accompanying the destruction of bubbles becomes obvious. In addition, since the shear speed during extrusion molding is relatively fast, the test piece is greatly stretched in the extrusion direction. As a result, the bubbles become flat shapes that extend greatly in the extrusion direction. It can be considered that when the test piece is heated in an atmosphere above the glass transition temperature of such a polycarbonate resin, the bubbles in the test piece shrink greatly in the extrusion direction, and the dimensional change rate of Comparative Examples 1 to 3 and 8 to 10 becomes larger. It can be considered that such a greatly extended flat-shaped bubble further reduces the density of the test piece, thereby reducing the bending elastic modulus of the test piece and making the test piece easy to destroy. At the same time, the evaluation of the vacuum molded product also becomes "C", so it becomes a test piece that is not suitable for heating shaping. Generally, it can be said that the foamed molded body formed by polycarbonate resin has excellent lightness and mechanical strength. However, in the above test, the test pieces of Comparative Examples 1 to 3 and 8 to 10 could not obtain excellent bending elastic modulus and impact properties. Furthermore, in Comparative Examples 4 and 11, N2 was used as the blowing agent, the thickness ratio of the outer skin layer to the coextruded sheet ((t1+t2) / T) was 0.05, and the density was 0.36 g / cm 3, but it is not possible to obtain excellent bending elastic modulus and impact properties. On the other hand, as described above, in the test pieces of Examples 1 to 22, the density of the test pieces was set to 0.4 to 0.9 g / cm by taking into account the thickness (t1 + t2) of the outer skin layer relative to the thickness T of the test piece. 3 , it is possible to obtain excellent lightness and mechanical strength, and to achieve an improvement in the appearance design when heated under vacuum forming conditions.
[0146] Comparative Example 5 was good in mechanical strength and sheet appearance when heated, as in Examples 1 to 11, but the vacuum forming evaluation was "C". It is believed that the main reason was that the deflection temperature under load of the resin material of the outer skin layer was lower than the deflection temperature under load of the resin material of the core layer, and peeling of the outer skin layer and the core layer occurred at the corner of the molded product, and bulging was confirmed. When the deflection temperature under load of the resin material of the outer skin layer was set lower than the deflection temperature under load of the resin material of the core layer, the processing accuracy of the vacuum formability was poor.
[0147] Comparative Example 12 was good in mechanical strength and sheet appearance when heated, as in Examples 12 to 22, but the vacuum forming evaluation was "C". The main reason is believed to be that the glass transition temperature of the resin material of the outer skin layer was lower than the glass transition temperature of the resin material of the core layer, and the outer skin layer and the core layer peeled off at the corner of the molded product, and a bulge was confirmed. When the glass transition temperature of the resin material of the outer skin layer was set lower than the glass transition temperature of the resin material of the core layer, the result showed a lack of processing accuracy of vacuum formability.
[0148] Comparative Examples 6 and 13 are sheet-shaped test pieces made by injection molding. In the case of the test piece made by injection molding, an outer skin layer is formed on the surface of the test piece by the cooling rate distribution in the mold. The evaluation of "sheet expansion / bulging portion" in Comparative Example 4 is "C". It can be considered that since the resin forming the outer skin layer of the test piece made by injection molding contains a foaming agent, the foaming agent expands when heated, and a large and more bulging portion is generated on the surface of the test piece. Therefore, the molded body and the co-extruded sheet obtained by injection molding are differentiated.
[0149] In Comparative Examples 7 and 14, the "specific bending modulus" is 2.00 GPa·cm 3 / g, the evaluation of "sheet expansion / bulging part" was "B", and the evaluation of "presence of damage" was "A". That is, the mechanical strength of Comparative Example 7 and the appearance design when heated under vacuum forming conditions are relatively excellent. However, the density of Comparative Example 7 is greater than 0.9g / cm 3 , so lightweighting cannot be achieved.
[0150] Description of Reference Numerals
[0151] 1 coextruded sheet, 2 core layer, 3 outer skin layer, 4 outer skin layer, 5 decorative film, 11 bulging part, T thickness, t1 thickness, t2 thickness, t3 average thickness, t4 average thickness, t5 thickness.
Claims
1. A co-extruded sheet comprising a polycarbonate resin, comprising a core layer, a first skin layer and a second skin layer, wherein the core layer is formed of a foamed resin, the first skin layer is formed of a non-foamed resin and is laminated on one main surface of the core layer, and the second skin layer is laminated on the other main surface of the core layer, The resin material of the first skin layer and the second skin layer has a deflection temperature under load that is higher than the deflection temperature under load of the resin material of the core layer, The co-extruded sheet has a thickness of 0.4 to 0.9 g / cm 3 The density of , and satisfies the following formula (1), 0.10≤(t1+t2) / T≤0.5···(1) In formula (1), t1 represents the thickness of the first outer skin layer, t2 represents the thickness of the second outer skin layer, and T represents the thickness of the coextruded sheet.
2. A co-extruded sheet comprising a polycarbonate resin, comprising a core layer, a first skin layer and a second skin layer, wherein the core layer is formed of a foamed resin, the first skin layer is formed of a non-foamed resin and is laminated on one main surface of the core layer, and the second skin layer is laminated on the other main surface of the core layer, The resin material of the first skin layer and the second skin layer has a glass transition temperature higher than the glass transition temperature of the resin material of the core layer, The co-extruded sheet has a thickness of 0.4 to 0.9 g / cm 3 The density of , and satisfies the following formula (1), 0.10≤(t1+t2) / T≤0.5···(1) In formula (1), t1 represents the thickness of the first outer skin layer, t2 represents the thickness of the second outer skin layer, and T represents the thickness of the coextruded sheet.
3. The coextruded sheet according to claim 1 or 2, wherein when the coextruded sheet is heated at 250°C for 30 minutes, an average thickness t3 of the coextruded sheet after heating is 1.5 times or less relative to an average thickness t4 of the coextruded sheet before heating.
4. The coextruded sheet according to claim 1 or 2, The coextruded sheet includes a bulging portion generated on the surface of the coextruded sheet due to the heating when the coextruded sheet is heated in a heating atmosphere at 250° C. for 30 minutes. The thickness t5 of the coextruded sheet including the bulging portion is 1.5 times or less of the average thickness t4 of the coextruded sheet before heating, The heated coextruded sheet has a surface area of 100 cm 2 There is less than one said bulge.
5. The coextruded sheet according to claim 1 or 2, When the coextruded sheet is heated in a heating atmosphere at 250° C. for 30 minutes, the average thickness t3 of the coextruded sheet after heating is 1.5 times or less relative to the average thickness t4 of the coextruded sheet before heating. The co-extruded sheet includes a bulged portion generated on the surface of the co-extruded sheet due to the heating, The thickness t5 of the coextruded sheet including the bulging portion is 1.5 times or less of the average thickness t4 of the coextruded sheet before heating, The heated coextruded sheet has a surface area of 100 cm 2 There is less than one said bulge.
6. The coextruded sheet according to claim 1 or 2, When the coextruded sheet is heated at 200° C. for 30 minutes, the coextruded sheet has a dimensional change rate of −5% to 0% in at least one of an extrusion direction and a width direction perpendicular to the extrusion direction in a plan view.
7. The coextruded sheet according to claim 1 or 2, wherein the coextruded sheet has a thermal conductivity of 1.5 GPa·cm 3 / g or more specific flexural modulus. 8 . The coextruded sheet according to claim 1 , wherein the polycarbonate resin contained in the first skin layer and the second skin layer has a melt volume flow rate of 1.0 to 5 times that of the polycarbonate resin contained in the core layer. 9 . The coextruded sheet according to claim 1 , wherein the resin material of the first skin layer and the second skin layer has a deflection temperature under load of 5° C. or more relative to the deflection temperature under load of the resin material of the core layer.
10. The coextruded sheet according to claim 2, wherein the resin material of the first and second skin layers has a glass transition temperature of 5°C or more relative to the glass transition temperature of the resin material of the core layer. 11 . The coextruded sheet according to claim 1 , wherein the core layer has a foaming ratio of 1.6 to 3.3 times.
Citation Information
Patent Citations
Polymeric sheets, methods for making and using the same, and articles comprising polymeric sheets
CN105026472A
Hollow body made of thermoplastic resin and preparation thereof
JP1990269033A
Base material for forming interior material for automobile
JP1996072628A
Multilayered resin sheet and its production
JP1997286079A
Laminated sheet and production thereof
JP2001071426A